Lactobacillus reuteri maintains intestinal epithelial regeneration and repairs damaged intestinal mucosa. (3rd July 2020) - Wu, Haiqin; Xie, Shuang; Miao, Jinfeng; Li, Yuchen; Wang, Zhihua; Wang, Minjuan; Yu, Qinghua
ABSTRACT: Little is known about the regulatory effect of microbiota on the proliferation and regeneration of ISCs. Here, we found that L. reuteri stimulated the proliferation of intestinal epithelia by increasing the expression of R-spondins and thus activating the Wnt/β-catenin pathway. The proliferation-stimulating effect of Lactobacillus on repair is further enhanced under TNF -induced intestinal mucosal damage, and the number of Lgr5 + cells is maintained. Moreover, compared to the effects of C. rodentium on the induction of intestinal inflammation and crypt hyperplasia in mice, L. reuteri protected the intestinal mucosal barrier integrity by moderately modulating the Wnt/β-catenin signaling pathway to avoid overactivation. L. reuteri had the ability to maintain the number of Lgr5 + cells and stimulate intestinal epithelial proliferation to repair epithelial damage and reduce proinflammatory cytokine secretion in the intestine and the LPS concentration in serum. Moreover, activation of the Wnt/β-catenin pathway also induced differentiation toward Paneth cells and increased antimicrobial peptide expression to inhibit C. rodentium colonization. The protective effect of Lactobacillus against C. rodentium infection disappeared upon application of the Wnt antagonist Wnt-C59 in both mice and intestinal organoids. This study demonstrates that Lactobacillus is effective at maintaining intestinal epithelial regeneration and homeostasis as well as at repairing intestinal damage after pathological injury and is thus a promising alternative therapeutic method for intestinal inflammation.